MENINGKATKAN KEMAMPUAN KOGNITIF ANAK MELALUI PEMBELAJARAN TEMATIK DENGAN METODE EKSPERIMEN BERCOCOK TANAM DI KELOMPOK B - kristina wahyu cahyaningsih; dita debita fajar utami; Rohmalina Rohmalina (CERIA (Cerdas Energik Responsif Inovatif Adaptif), 2019)
The teacher's job in designing and implementing learning requires a variety of knowledge, skills, and perhaps not all teachers have the ability to cultivate, presenting a learning theme that can dig into all the potential of the child's own. The method used tends to be monotonous, so learning becomes boring for the child. Based on that, the basic reason for the problem is that through thematic learning with experimental method of planting can improve the cognitive ability of child group B?. The purpose of this research is to know the thematic learning activities with the methods of planting experiments performed in group B that can improve the cognitive ability of children. This study uses a qualitative approach with a descriptive method. The process of thematic learning is done adapted to the theme that is running, namely the theme of plants, on the implementation through Taha-the preparation stage of syllabus such as drafting RPPM and RPPH, activities divided into 3 phases: the core activities, activities End and reflection activities. Based on the results of thematic learning with suitable planting methods, it has an impact on improving the cognitive abilities of child group B. It can be seen from several indicators of cognitive assessment of children before and after planting methods indicates optimal development.